The Influence of Brand Image and Electronic Word of Mouth on Customer Loyalty in Shopee Application Users and Gender as Moderator Variables - Herra Azzahro, Dhyvha; Rubiyanti, Nurafni (The International Journal of Business Review (The Jobs Review), 2023)
:This study aims to determine the effect of brand image and electronic word of mouth on customer loyalty in Shopee application users and gender as a moderating variable. The approach used is descriptive quantitative research with SMARTPLS 4.0 analysis. Shopee application users are the study population. The sampling method is non-probability sampling of 211 respondents from purposive sampling. The results showed that brand image and electronic word of mouth had a significant positive effect on customer loyalty using Shopee. Gender moderates brand image positively and not significantly, but gender moderates electronic word of mouth positively and insignificantly